LEXICO-SEMANTIC AND STRUCTURAL CHARACTERISTICS OF LATIN TERMS TO DENOTE "SAPRONOSES" - Синиця, Валентина (Modern engineering and innovative technologies, 2022)
Scientific ideas about laxative diseases have been accompanied by the emergence of appropriate terminology. Latin terminology of sapronic diseases is represented mainly by one-word terms. According to the structure, they are divided into simple non-deriv